'No nuts please': Food allergen management in takeaways. (September 2018) - Soon, Jan Mei
Abstract: There is an increasing number of food allergic reactions occurring in food services including takeaways. This study investigated the food allergy knowledge, attitude and practices of staff in takeaways. Although more than half of the takeaways' staff (n = 28) demonstrated good food allergy knowledge, there still exists some misunderstanding among the respondents. There were confusion about lactose intolerance and milk allergy, a third of the takeaways' staff were uncertain that hands could transfer allergens. Almost half of the respondents were not aware of the danger of offering water to dilute a food allergen to stop the reaction Experienced staff and managers/owners reported more positive attitude and higher frequency of good food allergen management practices. Respondents also strongly agreed that customers should inform staff if they have food allergies. However, takeaways' staff would enquire customers if they need allergen information when taking orders over the telephone. Clear communication between front service staff, customers and kitchen crew are important and should be established and meals verified with cooks to ensure safe meals are prepared. Managers or owners should also strongly encourage their staff to participate in food allergy training. Food Standards Agency has set up a free food allergy online training that would be a valuable addition to food businesses. Highlights: 43% (12) of takeaways' staff would mistakenly offer water to dilute a food allergen to stop the reaction. Takeaways' staff unanimously agreed it is customers' responsibility to inform them of their food allergies. Managers and owners were confident they can handle a food allergy emergency in the takeaways compared to kitchen crew.